Pengembangan Sistem Informasi Data Perumahan Pada Dinas Perumahan dan Permukiman Kota Balikpapan : Development of a Housing Data Information System at the Housing and Settlements Office of the City of Balikpapan - Dhany Dwi Kurniawan; Hariyady; Ilyas Nuryasin (Jurnal Repositor, 2023)
The Housing and Settlements Office of Balikpapan City needs information system support. Information systems needed to help reduce document management problems. More efficient document management is the main facility or feature of the application. So that users can take advantage of the system easily and very transparently. This study aims to develop an online registration information system (IMB) for building permit services and billing services for the City Hall of Balikpapan. The system development method is the prototype method. The prototype method is an excellent method in the system development process because it overcomes misunderstandings. User requirements analysis arises when the user cannot clearly define his needs. the application of this prototype method has produced 9 kinds of features at the needs analysis stage. The combination of the features for searching for housing locations and viewing housing data features is made into 1 interface design because of the close cohesion of these features. All of these interface designs have been successfully implemented using the PHP programming language and mysql database. The results of black box testing show that all features are running well.